KAJIAN PEDAGOGIK TERHADAP PERANAN LAGU ANAK SEBAGAI MEDIA INTERAKSI PEDAGOGIS PADA PENDIDIKAN ANAK USIA DINI DI TAMAN KANAK-KANAK - Rian Sri Nugroho, - (2022)
Pedagogy is a science that studies about how to educate children or the science of education. Children as humans who still need guidance from adult humans will always depend and develop according to the stages of development they go through. Early Childhood Education is one of the areas of study of pedagogics, early childhood education is certainly based on the educational situation that occurs where you will see how the child's character is, and it will be known how or the learning process to achieve educational goals. At an early age, namely 0-2 years, children are in the sensorimotor stage, while 3-8 are in the pre-operational stage. In this stage, children tend to imitate what they see, so that a good role model is needed so that children imitate good things too. The learning process for early childhood is learning while playing. Therefore, this process requires an approach that attracts children so that they can follow it, salted games are carried out by early childhood educators to foster a sense of pleasure and joy in children. The use of songs in a child's game will certainly greatly affect the condition of the child's soul, because the song is a form of expression from within the child's soul so that motivation arises to follow the learning process. Pedagogic views that the role of the teacher is to lead children to the gate of adulthood. Keyword: earlychildhood, pedagogic, song